Oltre i confini Le imprese "leggere" italiane e i mercati internazionali nel XIX e XX secolo - Mellinato, Giulio; Prosperi, Laura; Varini, Valerio (Geostoria del territorio, 2021)
The book investigates some aspects of the Italian economic development looking at some usually forgotten cases of international success: the small-medium enterprises specialized in "light" productions, such as food, beverages, and apparel. These firms have shown a peculiar ability to adapt, in order to cope with the instabilities of the international markets, modifying both their organization and their business strategies, elaborating an unusual entrepreneurial style, more attentive to the resources, constraints and vulnerabilities of the context.